5(t-4)+7t=4(3t+3)-11

Simple and best practice solution for 5(t-4)+7t=4(3t+3)-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(t-4)+7t=4(3t+3)-11 equation:


Simplifying
5(t + -4) + 7t = 4(3t + 3) + -11

Reorder the terms:
5(-4 + t) + 7t = 4(3t + 3) + -11
(-4 * 5 + t * 5) + 7t = 4(3t + 3) + -11
(-20 + 5t) + 7t = 4(3t + 3) + -11

Combine like terms: 5t + 7t = 12t
-20 + 12t = 4(3t + 3) + -11

Reorder the terms:
-20 + 12t = 4(3 + 3t) + -11
-20 + 12t = (3 * 4 + 3t * 4) + -11
-20 + 12t = (12 + 12t) + -11

Reorder the terms:
-20 + 12t = 12 + -11 + 12t

Combine like terms: 12 + -11 = 1
-20 + 12t = 1 + 12t

Add '-12t' to each side of the equation.
-20 + 12t + -12t = 1 + 12t + -12t

Combine like terms: 12t + -12t = 0
-20 + 0 = 1 + 12t + -12t
-20 = 1 + 12t + -12t

Combine like terms: 12t + -12t = 0
-20 = 1 + 0
-20 = 1

Solving
-20 = 1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x+67=5x+31 | | -26.04/-6.2= | | 6X-1=1X+8 | | 4x+2(6+3x)=2 | | 3cos^2-4cos=0 | | [2x-5]-2=3 | | -3x+20=0 | | y=-25cos(2x) | | 2x=9-2 | | 2+6(2x-1)=4(3x+1) | | 1=I | | A^2+18a=n | | 56y-560=y+23 | | 87-5x=22x+15 | | 28x-1=26x+1 | | sen^2(x)=0.1022 | | sin^2(x)=0.1022 | | Y=-2×/3= | | 1+ln(x+2)=0 | | A^2+42=c^2 | | 102=2w^2+14 | | 0=2x^2-96 | | y=3x-2lnx | | 13/20-3/5 | | sin^2(2x)+cos^2(2x)= | | m/6=21-m | | y+36=3x | | .625x=5 | | 8x^2+36x-40=0 | | 3²×=1/27 | | 3(cx+5)=45 | | 11x-22=7x+34 |

Equations solver categories